PERAN MEDIA DIGITAL DALAM MENINGKATKAN EFEKTIVITAS KOMUNIKASI LINTAS BUDAYA PADA KOMUNITAS MULTINASIONAL DI INDONESIA - Ayu Souterya Alkatiri; Nadia Naema Sisilia Yuniati Lodo; Kristiana Lipat Samon; Mali, Maria Muliani; Mas’ud, Fadil; Benu, Alfret (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article explores the role of digital media in enhancing the efficiency of intercultural communication within multinational communities in Indonesia. Drawing on a literature review of various journals, academic books, and research reports, the study highlights that platforms such as Zoom, WhatsApp, Google Workspace, and social media significantly improve communication speed, expand access to information, and foster intercultural collaboration. Despite these advantages, several challenges persist, including cultural misunderstandings, limited digital literacy, and difficulties in interpreting nonverbal cues. The effectiveness of intercultural communication through digital media largely depends on users’ communication competence, cultural sensitivity, and their ability to utilize technology effectively. Therefore, strengthening education and training in digital communication is essential to promote harmonious interactions within multinational communities.